The Effect of Calf Raise Exercise on Heart Rate, Oxygen Saturation, and Blood Pressure in Anesthesiology Nursing Students - Astika Nur Rohmah; Riska Risty Wardhani; Ratih Kusuma Dewi; Gatot Suparmanto (Indonesian Journal of Global Health Research, 2025)
Physical exercise is a body activity that is carried out in a planned, structured and repetitive manner with the aim of improving or maintaining physical fitness and overall health. The busyness experienced by students in terms of theoretical and practical learning makes students do less physical exercise, and this can have implications for decreased muscle flexibility and the risk of muscle injury. Lack of physical exercise has a significant impact on the cardiovascular system, especially on heart rate (HR), oxygen saturation (SpO2), and blood pressure (BP). The purpose of this study was to determine the effect of the calf raise exercise on heart rate, oxygen saturation and blood pressure. This research method is using a pre-experimental with a pre-post one-group design. This research method is using a pre-experimental with a pre-post one-group design. The number of samples in this study was 170. Using the total sampling technique by using inclusion we’re resting HR less than 100 x/min and BP within normal limits, namely systolic less than 120 mmHg and diastolic less than 110 mmHg, the statistical test in this study was the Friedman test. The mean results after the calf raise training for heart rate were 93.47±8.65, oxygen saturation 98.27±1.26, systolic blood pressure 120.28±10.97, and diastolic blood pressure 79.97±7.25. The conclusion of this research is that there are differences in heart rate variables, oxygen saturation, blood pressure at six measurement time points with a p-value of 0.000 each.